Availability and access to long-term inpatient rehab centers in north Tshwane, Gauteng - Komane-Mnguni, Rorisang G.; Mkhize, Nonhlanhla M.; Mfolo, Tshepiso; Madiba, Thomas K. (Health SA = SA Gesondheid, 2025)
Background: Substance abuse is increasing in South Africa with research indicating a lack of access to public drug rehabilitation centres in all provinces of the country. The insights of recovering substance abusers in terms of access to centres remain a gap in the north of Tshwane. Aim: The study explored the recovering substance abusers’ views or perspectives on the accessibility of long-term inpatient substance abuse rehabilitation centres. Setting: South African National Council on Alcoholism and Drug Dependence (SANCA) centers in Soshanguve and Hammanskraal. Methods: The qualitative study involved recovering substance abusers undergoing treatment at two outpatient substance rehabilitation centres in the north of Tshwane. The participants were interviewed using a semi-structured questionnaire which explored their views and perceptions and experiences on the accessibility to rehabilitation centres. Results: Saturation was reached at 13 male participants between 29 years and 35 years of age. The interviews were transcribed and translated, and five distinct themes were identified. The themes identified were: rehabilitation is mindset-related; long waiting times translated into continuous substance abuse; peer pressure; no jobs or skills to keep busy; and a lack of trust within the community. Four of the themes were attributed to enabling factors for their substance abuse. Conclusion: Long waiting times, few rehabilitation centres, stigma, the lack of jobs and skills were identified as barriers to access rehabilitation centres. Contribution: The study contributes to the body of literature exploring access problems in rehabilitation centres from the perspective of recovering drug addicts. It provides insights into risk factors that exacerbate the scourge of substance abuse in the north of Tshwane.